Volatile and Primary Compounds of Marsdenia brunoniana Leaves and Fruits via SPME-GC-MS Assay - Hariani , S.A; Kuswati Kuswati; Vitriyani A; Kurniawan A (BIOEDUKASI, 2023)
The genus Marsdenia is an essential genus with abundant phytochemistry. Its bioactive compounds contribute to the bioactivity of Marsdenia as drugs, biological control agents, and plant's essential oils. Marsdenia brunoniana is found wild in several places in Indonesia. There are inadequate reports in the literature concerning the chemical profiles of M. brunoniana. SPME-GC-MS is a fast, versatile, and feasible technique to identify volatile and primary compounds for further utilization of M. brunoniana. Leaves have 25 types of volatile compounds and 20 varieties in the fruit. The dominance of compounds in leaves and fruits include D-mannitol (sugar group), Octadecatrienoic acid, methyl ester; and Hexadecanoic acid (fatty acid group); Nonacosane; and Dodecanamine, N, N-dimethyl. All components have recommended functions and have been tested for bioactivity based on reference records. The information provided can be used as an initial reference for further use and testing of M. brunoniana.